Quotation errors related to the Distal Radius Acute Fracture Fixation Trial paper. (July 2021) - Cay, Peter; Leung, Brook; Curlewis, Keegan; Stone, Andrew; Roper, Tom; Ricketts, David
Quotation error is an inaccuracy in the assertions made by authors when referencing another's work. This study aimed to assess the quotation errors in articles referencing the Distal Radius Acute Fracture Fixation Trial (DRAFFT). A literature search was performed to identify all citations of DRAFFT from 2014 to 2020. The relevant publications were assessed by two reviewers using a validated framework of error classification. There were 83 articles containing references to DRAFFT. There was substantial agreement between the two reviewers (Kappa coefficient 0.66). We found 22/83 (28%) of articles contained an error, with one article containing two errors. There were 12 major errors, which were not substantiated by, were unrelated to or contradicted the findings of DRAFFT, and 11 minor errors, including numerical inaccuracies, oversimplification or generalization. This study highlights that a significant number of articles inaccurately quote DRAFFT. Authors and journals should consider checking the accuracy of key referenced statements.